![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
76个回答
展开全部
39+61×45
=39+(60+1)×45
=39+2700+45
=2739+45
=2784
=39+(60+1)×45
=39+2700+45
=2739+45
=2784
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
39+61×45
=39+60×45+45
=39+45+60×5×9
=84+300×9
=84+2700
=2784
=39+60×45+45
=39+45+60×5×9
=84+300×9
=84+2700
=2784
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
39+61×45
=39+(60+1)×45
=39+(60×45+1×45)
=39+(2700+45)
=39+2745
=2745+40-1
=2785-1
=2784
=39+(60+1)×45
=39+(60×45+1×45)
=39+(2700+45)
=39+2745
=2745+40-1
=2785-1
=2784
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
39+61x45
=39+(60+1)ⅹ45
=39+2700+45
=2784
=39+(60+1)ⅹ45
=39+2700+45
=2784
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
39+61*45
=39+45*(60+1)
=39+2700+45
=2700+84
=2784
=39+45*(60+1)
=39+2700+45
=2700+84
=2784
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询